THE ROLE OF THE DEVELOPMENT OF OPERATIONAL MANAGEMENT CONCEPTS IN THE INNOVATIONS MANAGEMENT - Y. Kafiyatullina; E. Panfilova (Вестник университета, 2018)
The role of the development of operational management concepts in order to pro-vide systematic support for the organization’s innovation activities has been considered. It has noticed, that each concept is an organizational innovation for the implementation of oper-ational activities, with each subsequent does not contradict the previous one, which makes possible simultaneous application of several in order to improve the efficiency of the organ-ization. It has concluded, that the integrated application concept allows you to create an or-ganizational environment for creating and implementing innovations on an ongoing basis. The combination of elements of different concepts, methodological recommendations of op-erational management and innovation management is reflected in the integration approach based on digital technologies.